BUDAYA TEKTONIKA WOLOGAI ENDE, NUSA TENGGARA TIMUR: Sebuah Seni Berkonstruksi Rumah Adat Desa Wologai Tengah, Kecamatan Detusoko, Warisan Leluhur Wawo - Ata Lio di Bawah Kaki Gunung Lepembusu - Reginaldo Ch. Lake (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2015)
Title: Culture of Tectonics Wologai – Ende, a Traditional House Constructed of Art Central Wologai Village, District Detusoko, Ancestral Heritage, Waeo – Ata Lio Under the Foothills of Lepembusu As a counterbalance to globalization in the field of architecture, an in-depth understanding of local architecture had been seen as an opportunity for a region to play an active role in the global era. One way to develop an understanding of local architecture is through the art of construction, or widely known as tectonics. The word architecture itself was known to derive from the word archi, which means master and tekton, which means woodworker (carpenter) or builder. Thus, the study of tectonics was important to understand how architects express their ideas through an integrated architectural - structural system. Unfortunately, profound research into this field has rarely been conducted so far. This study aims to an understanding of architectural tectonics in Wologai, Flores, Nusa Tenggara Timur. As one of the oldest village in Flores, the indigenuous people of Wologai had been known for surviving the pressures of the developing world whilst maintaining their unique culture that were reflected in their vernacular buildings. This study consists of the following steps: Firstly, to record how local builders built their architecture through observation and interviews. Secondly, to develop an understanding about architectural tectonics based on related literature. The last step was to analyse and formulate architectural tectonics of Wologai vernacular architecture.